Filsafat Pendidikan Pancasila dalam Tinjauan Ontologi, Epistimologi, dan Aksiologi - Sindi Pramita; Salminawati Salminawati; Misra Nova Dayantri; Tri Abdi Syahputra (Journal on Education, 2024)
The fundamental question in this study is whether the implementation of the nation's national education system has reflected the philosophical views rooted in Pancasila. The research method applied is library research or can also be called Library Research. Library research is a type of research that uses the necessary data from books, dictionaries, documents, magazines, articles, journals, and other similar sources. The results of this study, among others, are that the Pancasila education philosophy as the spirit of the national education system in Indonesia must be truly lived as a source of value and reference in strategic planning in the field of education in Indonesia. The philosophy of Pancasila Education must be implemented in a real and consistent manner so that Indonesian human development as mandated in the great ideals of the Indonesian nation can be achieved with the basic principles of Pancasila values, namely the principle of religiosity, the embodiment and appreciation of human values, holding fast to the spirit of unity as a nation, the spirit of respect for differences and respect for democratic life and the embodiment of justice values, all of which must be realised through a dignified educational process.